2019
DOI: 10.1108/ejim-12-2018-0276
|View full text |Cite
|
Sign up to set email alerts
|

How R&D originality affects open innovation under knowledge spillovers?

Abstract: Purpose The purpose of this paper is to investigate how R&D originality functions in an open innovation process after the introduction of knowledge spillovers (KSs). Design/methodology/approach To examine the research framework, the authors use hierarchical regression based on questionnaire data from 211 emerging enterprises in China. Findings Consistent with the proposed framework, the authors find that the KS effect mediates the positive relationship between openness and innovation performance. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
(166 reference statements)
0
11
0
Order By: Relevance
“…Hinteregger et al (2019) investigated that inbound and coupled innovation has a positive influence on FP and Oltra et al (2018) explored that inbound, outbound and coupled innovation has a positive effect on FP. In terms of negative results, Caputo et al (2016) and Wang and Jiang (2020) pointed out that OI has a negative effect on FP. Further Flor et al (2017) and Mendeza et al (2015) identified negative effects between inbound innovation and FP.…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hinteregger et al (2019) investigated that inbound and coupled innovation has a positive influence on FP and Oltra et al (2018) explored that inbound, outbound and coupled innovation has a positive effect on FP. In terms of negative results, Caputo et al (2016) and Wang and Jiang (2020) pointed out that OI has a negative effect on FP. Further Flor et al (2017) and Mendeza et al (2015) identified negative effects between inbound innovation and FP.…”
Section: Research Findingsmentioning
confidence: 99%
“…Many scholars argue that the implementation of OI have a positive impact on FP (Mazzola, Bruccoleri, & Perrone, 2016;Oltra et al, 2018;Popa, Acosta, & Conesa, 2017). Some scholars noted an inverted U-shaped relationship (Caputo, Lamberti, Cammarano, & Michelino, 2016) or even a negative effect on FP (Wang & Jiang, 2020). Due to the inconsistency and inconclusive arguments, there is incomplete literature and an ongoing debate on the OI and FP.…”
Section: Introductionmentioning
confidence: 99%
“…Ghebrihiwet (2019) took the extractive industry in South Africa as an example and expounded that the technology spillover effect has a positive effect on the development of domestic technology in resource-rich countries. Wang and Jiang (2019) employed the hierarchical regression method to study the linkage of openness and innovation performance. Based upon empirical analysis, they found that there is a significant positive relationship between openness and innovation performance.…”
Section: The Technology Spillover Effect Of Multinational Enterprises...mentioning
confidence: 99%
“…Moreover, through this exchange of resources and information, a firm is able to implement new competitive moves such as product promotion and sales incentives (Wang and Jiang, 2020), leading to enhanced innovativeness performance. Thus, trust allows firms to develop more radical cooperative projects (Akçomak and ter Weel, 2006), resulting in more effective innovativeness.…”
Section: Towards a Configurational Approachmentioning
confidence: 99%
“…In the literature, social capital is a well-recognized factor in the acquisition of external knowledge through the relationships that individuals and social units possess (Nahapiet and Ghoshal, 1998;Wang and Jiang, 2020). Relational social capital addresses the personal relationships that firms have established, with RT being its essential component (Kaasa, 2009).…”
Section: Introductionmentioning
confidence: 99%